2015
DOI: 10.3390/rs71012942
|View full text |Cite
|
Sign up to set email alerts
|

Detecting the Temporal Scaling Behavior of the Normalized Difference Vegetation Index Time Series in China Using a Detrended Fluctuation Analysis

Abstract: Abstract:Vegetation is an important part of terrestrial ecosystems. Although vegetation dynamics have explicit spatial and temporal dimensions, the study of the temporal process is in its infancy. Evaluation of temporal scaling behavior could provide a unique perspective for exploring the temporal nature of vegetation dynamics. In this study, the Global Inventory Modeling and Mapping Studies (GIMMS) Normalized Difference Vegetation Index (NDVI) was used to reflect vegetation dynamics, and the temporal scaling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 57 publications
(100 reference statements)
1
5
0
Order By: Relevance
“…The spatial pattern of Hurst exponents in NDVI reveals the spatial heterogeneity in the temporal scaling behavior of the NDVI that rhymes with the individual ecological regions. The SD of the exponent is 0.18 and the range is from 0.0 to 1.3 over the period 1982 -2011, while the range of exponent over China is from 0.4843 to 1.2215 with SD of 0.08 over the period 1982 -2006 [68]. The spatially averaged exponent over West Africa for 30 years is 0.58 while that of China is 0.78 over a period of 25 years, which implies China's vegetation is more persistent than West Africa.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…The spatial pattern of Hurst exponents in NDVI reveals the spatial heterogeneity in the temporal scaling behavior of the NDVI that rhymes with the individual ecological regions. The SD of the exponent is 0.18 and the range is from 0.0 to 1.3 over the period 1982 -2011, while the range of exponent over China is from 0.4843 to 1.2215 with SD of 0.08 over the period 1982 -2006 [68]. The spatially averaged exponent over West Africa for 30 years is 0.58 while that of China is 0.78 over a period of 25 years, which implies China's vegetation is more persistent than West Africa.…”
Section: Discussionmentioning
confidence: 93%
“…[67] studied long range correlation in vegetation over the greater Khingan Mountains using DFA method and results indicated that NDVI have self-similar properties. [68] evaluated the temporal scaling behavior of NDVI over China using DFA method and the analysis suggested that the NDVI time series displays strong long-range correlation throughout most of China with regional variability in the Hurst exponent h.…”
Section: Introductionmentioning
confidence: 99%
“…Although the accuracy of wetland delineation needs to be further improved, this kind of research will lay the foundation for exploring methods of wetland monitoring at a low cost on a reserve scale in the future. It is possible to map more distinct wetland boundaries with lesser confusion and greater accuracies using hyperspectral data or high resolution images or time-series data (Feyisa et al, 2014;Guo et al, 2015). The combination of an automated water extraction index and the related digital elevation models could be used to establish models for wetland delineation in the future (Martinez-Lopez et al, 2014).…”
Section: Further Research Suggestionsmentioning
confidence: 99%
“…So, the annual variation of vegetation study is an important part for the understanding and management of the environment. The inter-annual and interseasonal variability of NDVI has been studied by many scholars (Anyamba & Eastman, 1996;Eastman & Fulk, 1993;Guo, Zhang, Yuan, Zhao, & Xue, 2015;Li & Kafatos, 2000;Myneni, Los, & Tucker, 1996;Nemani et al, 2003;Sarkar & Kafatos, 2004). Most of their studies were focused on the factors behind the natural oscillation of natural vegetation.…”
Section: Introductionmentioning
confidence: 99%
“…Sarkar and Kafatos (2004) studied on the Indian subcontinent for several years to study the variability of vegetation and found the dominance of local climate anomaly in determining the vegetation. Several kinds of datasets, e.g., NOAA-AVHRR, SPOT-VGT, MODIS and GIMMS have been used (NOAA-AVHRR, SPOT-VGT, MODIS and GIMMS) to study the variability of vegetation at the local, regional and global scale (de Jong, de Bruin, de Wit, Schaepman, & Dent, 2011;Detsch, Otte, Appelhans, Hemp, & Nauss, 2016;Dubovyk, Landmann, Erasmus, Tewes, & Schellberg, 2015;Fensholt & Proud, 2012;Guo et al, 2015;Hou, Zhang, & Wang, 2011;Jeong, HO, GIM, & Brown, 2011;Lanorte, Lasaponara, Lovallo, & Telesca, 2014;Lu, Kuenzer, Wang, Guo, & Li, 2015;Martínez & Gilabert, 2009;Schucknecht, Erasmi, Niemeyer, & Matschullat, 2013;Sobrino & Julien, 2011;Teferi, Uhlenbrook, & Bewket, 2015;Zhao et al, 2013).…”
Section: Introductionmentioning
confidence: 99%